Enhanced bactericidal and in vivo wound healing potential of biosynthesized zinc oxide nanoparticles from psyllium mucilage. (21st October 2022) - Azam, Aiza; Muhammad, Gulzar; Aslam, Muhammad Shahbaz; Iqbal, Muhammad Mudassir; Raza, Muhammad Arshad; Akhtar, Naeem; Hussain, Muhammad Ajaz; Sajjad, Noreen; Syed, Asad; Bahkali, Ali H.; Shafiq, Zahid
Abstract : The multifunctional zinc oxide nanoparticles are synthesized using a cost‐effective, efficient, eco‐friendly, simple, and clean synthesis approach. Herein, we reported the antibacterial and wound healing potential of zinc oxide nanoparticles (ZnO‐NPs) prepared using psyllium gel (PG) as the reducing and stabilizing agent. The PG‐mediated zinc oxide nanoparticles (PG‐ZnO‐NPs) were characterized using UV–Vis, photoluminescence (PL), FTIR, XRD, Raman, and SEM. UV–Vis spectral studies confirmed the surface plasmonic resonance (SPR) band at 364 nm. PL results demonstrated the fluorescent or emission nature of PG‐ZnO‐NPs. FTIR analysis confirmed characteristic peaks at 873.82 and 619.88 cm −1 due to the tetrahedral coordination of zinc and the formation of the Zn‐O bond. XRD and Raman confirm the formation of PG‐ZnO‐NPs, whereas SEM analysis revealed PG‐ZnO‐NPs are rod‐shaped, having hexagonal prism‐like bases, and EDX exhibited the elemental composition of PG‐ZnO‐NPs. The as‐synthesized PG‐ZnO‐NPs possessed prominent microbicidal potential against gram‐positive ( Bacillus subtilis and Bacillus licheniformis ) and gram‐negative ( Escherichia coli and Salmonella shigella ) bacterial strains in terms of zone of inhibition (ZOI), minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC). In vivo biological investigations with mice show that the synthesized PG‐ZnO‐NPs possess outstanding biocompatibility and wound healing potential. PG‐ZnO‐NPs dressing significantly speeds up full‐thickness wound repair by triggering a decrease in MMP‐1 and MMP‐2 and escalating the mRNA levels of collagen types (I & III) and fibronectin. Thus, our work validates that the inclusion of PG‐ZnO‐NPs in dressing shows excellent potential for acute wound management. Abstract :